(untitled) (Bangladesh Journal of Child Health, 2017)
Infections are responsible for the majority of loss of life in children and vaccination has made enormous contribution to public health, including the eradication of one dreaded disease, small pox, and elimination of poliomyelitis from all but a handful of countries. Globally, immunization currently averts an estimated 2 to 3 million deaths every year. In Bangladesh it has prevented an estimated 2 million deaths from 1987- 2000, and continues to prevent approximately 200,000 deaths each year. WHO introduced EPI (Expanded Programme on Immunization) in 1977 at Alma-Ata, the capital of Kazakhastan for the underdeveloped countries. Subsequently Bangladesh has launched EPI programme. Recently AD (Auto Disable) syringes and vaccination against Hepatitis B, H. Influenzae, Measles-Rubella (MR) and Pneumococcus has been introduced in vaccination programme. In Bangladesh, immunization coverage of DPT/PENTA3 was only 16% in 1988 increased significantly to 69% in 1990, 81% in 2000, 90% in 2011and 92% in 2013 which was higher than global coverage of 84% in 2013 and comparable to first world countries. In Pakistan fully immunization coverage in 2010 was only 50%.9 Indian national full immunization coverage was 56% in 1990, 59% in 2000, 74% in 2010 and 74% in 2012 whereas in our country it was 52% in 1991, 53% in 2000, 79% in 2010, 80% in 2011and 81% in 2013 which signifies our excellent success for prevention of communicable diseases in successive years. So, EPI in Bangladesh has been recognized for its sustained high coverage and great contribution to the reduction of childhood morbidity and mortality and it received two GAVI best performance award in 2009 and 2012. Bangladesh J Child Health 2015; VOL 39 (2) :93-98